Functional borders, genetic fine structure, and distance requirements of cis elements mediating light responsiveness of the parsley chalcone synthase promoter. - Block, A (1990)
The genetic fine structure of cis-acting sequences previously shown to be necessary for light-regulated expression in the promoter of the parsley (Petroselinum crispum) chalcone synthase gene was analyzed. Site-directed mutations and changes in spacing between cis elements were measured in transient expression assays in parsley protoplasts. Clustered point mutations allowed assignment of functional borders. Single-base substitutions within a highly conserved cis element (box II/G box) defined a critical core of seven bases, 5'-ACGTGGC-3'. It is functionally equivalent to a second sequence-related element (box III), which could replace box II in an orientation-dependent manner. The activity of box II required the presence of another juxtaposed element (box I) at a defined distance. No distance requirement was observed between the two large separable promoter regions known to independently confer light-regulated expression. These data support our hypothesis that a cis-acting sequence that is present in a limited number of diversely regulated plant genes gains its functional capacity and specificity by combinatorial diversity involving flanking partner elements.